Ancient genomics and the origin, dispersal, and development of domestic sheep - Daly, Kevin; Bradley, Daniel; Mattiangeli, Valeria (My University, 2025)
The origins and prehistory of domestic sheep (Ovis aries) are incompletely understood; to address this we generated data from 118 ancient genomes spanning 12,000 years sampled from across Eurasia. Genomes from Central Türkiye ~8,000 BCE are genetically proximal to the domestic origins of sheep but do not fully explain the ancestry of later populations, suggesting a mosaic of wild ancestries. Genomic signatures indicate selection by ancient herders for pigmentation patterns, hornedness, and growth rate. While the first European sheep flocks derive from Türkiye, in a striking parallel with ancient human genome discoveries, we detect a major influx of Western steppe-related ancestry in the Bronze Age.
PUBLISHED
Keywords: Genetics; Genes & Society; Genetics